“Don’t Even Smoke But I’ll Buy That” Twitch as a New Venue for E-Cigarette Promotion - Hüseyin Küçükali; Hüseyin Küçükali (International Journal of Public Health)
ObjectivesThis study examines the covert promotion of e-cigarettes, specifically Juul, on the video live-streaming platform Twitch, focusing on the content and platform-specific dynamics that may influence its effectiveness.MethodsThis qualitative case study of a non-gaming Twitch stream included data from influencer conversations, viewer comments and visual elements. Thematic analysis, coding, and categorisation were conducted using ATLAS.ti.ResultsThe livestream, which attracted over ten thousand viewers, featured three friends vaping and discussing their personal experiences with Juul. Themes included curiosity, device sharing, and smoking cessation benefits. The stream fostered a casual, engaging atmosphere, with viewers interacting extensively with the influencers and also other viewers. Despite suspicions of industry sponsorship, viewers reacted positively and even joked about the sponsorship. Several viewers, including those who claimed not to smoke, expressed interest in Juul.ConclusionThe study highlights concerns about the promotion of harmful commodities on Twitch, where strong community engagement, monetary incentives, and a lack of specific content policies create a conducive environment for such practices. This underscores the need for greater scrutiny and regulation of e-cigarette promotions on the platform.